2004
DOI: 10.1177/10883576040190030401
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Stories to Promote Independent Behaviors in Novel Events for Children With PDD-NOS

Abstract: This study investigated a previously undocumented use for Social Stories (Gray, 1994, 2000): preparation for a novel event. Three children With pervasive developmental disorder—not otherWise specified (PDD-NOS) participated in novel activities Within the routine setting of their Weekly speech—language therapy sessions. During intervention, Social Stories Written for the novel activities Were used to prepare the participants for the upcoming events. Independent participation during the novel events Was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 21 publications
1
61
1
3
Order By: Relevance
“…Other possible applications suggested by Gray (1998Gray ( , 2004, such as teaching academic skills, assisting students in novel events, and acknowledging students' achievements, remain largely unexplored in the research literature. For example, only two studies (Ivey et al 2004;Schneider and Goldstein 2009) examined the use of Social Stories to address difficulties in novel situations and transitions, characteristic of students with ASD (American Psychiatric Association 2000). Reynhout and Carter's (2006) metaanalysis resulted in similar conclusions, pointing to a limited use of Social Stories.…”
Section: Intervention Characteristicsmentioning
confidence: 98%
“…Other possible applications suggested by Gray (1998Gray ( , 2004, such as teaching academic skills, assisting students in novel events, and acknowledging students' achievements, remain largely unexplored in the research literature. For example, only two studies (Ivey et al 2004;Schneider and Goldstein 2009) examined the use of Social Stories to address difficulties in novel situations and transitions, characteristic of students with ASD (American Psychiatric Association 2000). Reynhout and Carter's (2006) metaanalysis resulted in similar conclusions, pointing to a limited use of Social Stories.…”
Section: Intervention Characteristicsmentioning
confidence: 98%
“…Sosyal öyküyle yapılan çalışmalar arasında arkadaşlarıyla oyun oynama, oyunu sürdürme ve oyuncaklarını paylaşma (Delano ve Snell, 2006;Pettigrew, 1998;Sansosti ve Powell Smith, 2008), sözel yönergelere tepki verme (Brownell, 2002;Rogers ve Myles, 2001), selamlaşma (Feinberg, 2002;Grigore ve Rusu, 2014;Litras, Moore ve Anderson, 2010;Reichow ve Sabornie, 2009) olarak uygun sosyal davranışların arttırılmasına yönelik çalışmaların yapıldığı görülmektedir. Bununla birlikte yüksek sesle okuma, konu ile ilgili yorumda bulunma (Hagiwara ve Myles, 1999) ve hikaye dersine katılımı arttırma (Ivey, Heflin ve Alberto, 2004) gibi var olan sosyal becerilerin geliştirilmesine yönelik yapılan çalışmalar da bulunmaktadır. Ayrıca gürültü yapma, tepinme (Kuttler, Myles ve Carlson, 1998), yemek sırasında bağırma (Rowe, 1999), arkadaşlarına gereksiz dokunma (Cullain, 2002), çığlık atma (Agosta, Graetz, Mastropieri ve Scruggs, 2004) gibi problem davranışların azaltılmasına yönelik olarak yapılan sosyal öykü çalışmaları da bulunmaktadır.…”
Section: Introductionunclassified
“…Technology offers carers the possibility of personalising stories by facilitating the use of graphic images, animated characters, digital pictures, video clips and sound files which suit the individual"s developmental age, learning style, reading ability, attention span and special interests. Some researchers have used multimedia (Hagiwara & Smith Myles, 1999), visual cues (Thiemann & Goldstein, 2001;Lorimer et al, 2002;Delano & Snell, 2006;Soenksen & Alper, 2006), verbal cues (Thiemann & Goldstein, 2001;Soenksen & Alper, 2006), music (Brownell, 2002), and personal photographs (Agosta et al, 2004;Ivey et al, 2004) to illustrate social stories and found that it helped children to understand the meaning behind the text. work environment (Smith, 2001).…”
Section: 2mentioning
confidence: 99%